Simulation analysis and experimental study on R290 substituting for R134a electric vehicle compressor - CHEN Jianhong; TAO Leren; HUANG Lihao; WANG Xiaofei; LI Xingjiang; CHEN Haonan (Zhileng xuebao)
Electric vehicles have different driving forces with traditional vehicles. New energy vehicles power is diversified. It is an important research direction to reduce power for new energy vehicles and to develop lower global warming potential (GWP) refrigerants for emission target. This article compares the thermodynamic performance of different refrigerants R134a and R290 through simulation, and builds a performance testing system for new energy vehicle compressors and study the effects of different refrigerants R134a and R290 on the performance of new energy vehicle compressors with different speed. The results showed that isentropic efficiency and volumetric efficiency of the compressor increase with the compressor speed, and the increase tends to be smooth after the rated speed. When using R290 refrigerant, the isentropic efficiency and volumetric efficiency of the compressor are slightly improved compared to using R134a refrigerant. The isentropic efficiency and volumetric efficiency of the compressor increase with the increase of evaporation temperature and are negatively correlated with condensation temperature. The comparison between the simulation results and experimental results of compressor power has good applicability, and other influencing factors need to be considered in the simulation at low and high speeds.